Profile of the Managers in the Destination Management Organisations (DMOS) in Slovakia - Bíziková, Viktória; Žitný, Rastislav (Journal of Posthumanism, 2025)
Effective destination management depends on skilled managers who use resources strategically. This research analyses the profiles of Slovak destination managers, examining their demographics, education, experience, roles, management styles and competencies. It answers the question: What characteristics characterise managers in Slovak destination management organisations? The quantitative survey was conducted with 40 managers in Slovakia. Basic statistical methods were used to analyse the data, including calculating frequencies and percentages for each category of respondents. The Mann-Whitney U-test was used to assess the significance of differences between groups of respondents. The findings indicate that most hold a university degree and have more than five years of experience. Interpersonal skills are paramount, with participative leadership dominating. Planning and organising are key functions. Managers excel in soft skills such as teamwork and motivation but struggle to improve in sales and marketing. Identifying this profile is crucial for enhancing training programmes and informed strategic decisions in Slovakia's tourism development.